Analisis Psikologi Sastra dalam Kumpulan Cerpen Kupu-kupu Kuning Ngindang di Candidasa karya I Ketut Sandiyasa - Pratiwi, Dwi Suryaning Intan; Suteja, I Wayan (Humanis, 2020)
This research entitled "Collection of Short Stories Kupu-Kupu Kuning Ngindang di Candidasa by I Ketut Sandiyasa Literary Psychological Analysis" by discussing three short stories entitled Tamplakan Limané Intan Pandini; Kupu-Kupu Kuning Ngindang di Candidasa; and Wayan Arya NgalihTunangan with psychological analysis of literature. This analysis aims to determine the structure and obtain a clear explanation about psychological aspects of the characters in the short story. This research uses structural and literary psychological theories The methods and techniques used in this study were divided into three stages; the stage of providing data using the listening method along with translation technique and note-taking technique, the stage of data analysis using qualitative method with descriptive analytic technique, the stage of presenting the results of analysis using informal methods with deductive techniques. In this study, it can be found the narrative structure such as incidents, plot, characters and characterizations, settings, themes, and moral value of the stories. Psychological aspects in the three short stories entitled Tamplakan Limané Intan Pandini; Kupu-Kupu Kuning Ngindang di Candidasa; and Wayan Arya Ngalih Tunangan in the collection of short stories Kupu-Kupu Kuning Ngindang di Candidasa including Id, Ego, and Super Ego (part of theory of literature psychology). Id in these short stories are seen in the mentality of the main and the secondary characters when performing an action for pleasure and self-satisfaction.  Ego in these short stories are seen in the mentality of the main and secondary characters when performing conscious actions. Super Ego in these short stories are seen in the psychological aspect of the main and secondary characters when doing an action based on a sense of remorse and self-introspection of the mistakes made.